Complete First Aid : Everything You Need to Know to Deal With Accidents, Emergencies & Illnesses - Bass, David, Kibel Maurice and Baker Rod (London New Holland, 2007)
A guide to first aid that offers information for coping with emergencies and illnesses and for avoiding accidents in the home. With a section devoted to babies and children, it offers practical advice and techniques to equip you with the skills for administering basic first aid, as well as tips for minimizing the risk of accidents in the home.
Include Pictures, Glossary and Index
Keywords: First aid in illness and injury. -- Emergency medicine -- Popular works